1982
DOI: 10.5014/ajot.36.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Stimulation Effect on Language Development in Mentally Retarded Children

Abstract: Effects of specific vestibular stimulation and speech therapy on language ability in mentally retarded children were examined. Thirty subjects were assigned to three treatment groups on the basis of the rank order of overall scores on the Porch Index of Communicative Ability in Children (PICAC). Group I received specific vestibular input in addition to specific speech therapy. Group II received specific speech therapy alone. Group III received general speech stimulation. Treatment was given during a 6-week per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Just under half of the studies (12/27) included only primary/elementary‐school aged participants from 5 to 11 years (Agbaria, 2020; Bagattoni et al, 2020; Bennett & Buckley, 2013; Burgoyne et al, 2012; Dessemontet et al, 2021; Drysdale & Porter‐Armstrong, 2008; Hong, 2012; Jacques & Townsend, 1998; Kantner & Clark, 1982; Litrownik et al, 1978; Saint‐Georges et al, 2020; Tanet et al, 2020; Wuang & Su, 2013), or children of various age ranges across 5–18 years (12/27) (Dessemontet et al, 2021; Grindle et al, 2021; Hessl et al, 2019; Janeslätt & Granlund, 2019; Kostulski et al, 2021; Lanfranchi et al, 2015; Lee et al, 2017; Lee et al, 2020; McDuffie et al, 2018; McPherson et al, 2017; Roberts‐Tyler et al, 2020; Sepúlveda & Heinze, 2013). Few studies (2/27) included only secondary‐school‐aged, adolescent participants aged 12–18 years (Baran et al, 2013; Maïano & Erraïs, 2001), and a single study described participants only as ‘children’ without specifying age (Balthazar & Sindberg, 1971).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Just under half of the studies (12/27) included only primary/elementary‐school aged participants from 5 to 11 years (Agbaria, 2020; Bagattoni et al, 2020; Bennett & Buckley, 2013; Burgoyne et al, 2012; Dessemontet et al, 2021; Drysdale & Porter‐Armstrong, 2008; Hong, 2012; Jacques & Townsend, 1998; Kantner & Clark, 1982; Litrownik et al, 1978; Saint‐Georges et al, 2020; Tanet et al, 2020; Wuang & Su, 2013), or children of various age ranges across 5–18 years (12/27) (Dessemontet et al, 2021; Grindle et al, 2021; Hessl et al, 2019; Janeslätt & Granlund, 2019; Kostulski et al, 2021; Lanfranchi et al, 2015; Lee et al, 2017; Lee et al, 2020; McDuffie et al, 2018; McPherson et al, 2017; Roberts‐Tyler et al, 2020; Sepúlveda & Heinze, 2013). Few studies (2/27) included only secondary‐school‐aged, adolescent participants aged 12–18 years (Baran et al, 2013; Maïano & Erraïs, 2001), and a single study described participants only as ‘children’ without specifying age (Balthazar & Sindberg, 1971).…”
Section: Resultsmentioning
confidence: 99%
“…Few (4/27) studies specified diagnosis by reporting: the presence of Down Syndrome (Bennett & Buckley, 2013;Burgoyne et al, 2012;Lanfranchi et al, 2015) or Fragile X Syndrome (Hessl et al, 2019). Two studies identified participants with intellectual disability from educational records: an Education and Health Care Plan in place (Grindle et al, 2021), or input from an educational psychologist (Drysdale & Porter-Armstrong, 2008) (Agbaria, 2020;Bagattoni et al, 2020;Baran et al, 2013;Dessemontet et al, 2021;Drysdale & Porter-Armstrong, 2008;Hessl et al, 2019;Hong, 2012;Jacques & Townsend, 1998;Janeslätt & Granlund, 2019;Kantner & Clark, 1982;Kostulski et al, 2021;Lee et al, 2017;Lee et al, 2020;Maïano & Erraïs, 2001;McDuffie et al, 2018;Roberts-Tyler et al, 2020;Wuang & Su, 2013). Seven studies included participants with moderate-severe or severe intellectual disability (Balthazar & Sindberg, 1971;Grindle et al, 2021;Lanfranchi et al, 2015;Litrownik et al, 1978;Sepúlveda & Heinze, 2013), two of which were published from the same cohort with an average DQ of 30 (Saint-Georges et al, 2020;Tanet et al, 2020).…”
Section: Age Gender and Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the many studies of vestibular functioning in adult schizophrenics, a number of authors have linked vestibular function to hyperkinesis (Bhatara, Clark, and Arnold 1978;Bhatara et al 1981), dyslexia and dyspraxia (Frank and Levinson 1976), neurosis (Barany 1906(Barany , 1907bBauer and Schilder 1919;Schilder 1933;Hallpike, Harrison, and Slater 1951;French 1952;Lidvall 1963;Dix and Hood 1970;Rakhmilevich 1975), anxiety (Miskolczy-Fodor 1961;Torok 1970b;Hoffman and Brookler 1978), infantile autism (Ritvo et al 1969;Ornitz et al 1974b;Clark and Gunsett 1978;Nelson, Nitzberg, and Hollander 1980) and childhood schizophrenia (Pollack and Krieger 1958;Colbert, Koegler, and Markham 1959), emotionally disturbed (Piggott et al 1976) and psychotic children (Zlotnik et al 1971), and high-risk infants (Fish and Dixon 1978). The question of whether stimulating the vestibular system might produce change in clinical condition has been investigated with respect to schizophrenia (King 1974;Bailey 1978), autism (Freeman, Frankel, and Ritvo 1976), and developmental delays (Kantner et al 1976;Magrun et al 1981;Kantner, Kantner, and Clark 1982). Mirabile and Glueck (1980) have studied the relationship between motion sickness susceptibility and psychosis.…”
mentioning
confidence: 99%
“…Increased use of vestibular stimulation in clinical settings [1][2][3] has generated concern over potential dan gers of indiscriminate application of this form of sensory input. Specifically, clinicians have reported seizure activity in seizure-prone children after appli cation of vestibular stimulation.…”
mentioning
confidence: 99%